Clinical and endoscopic assessment of gastric state in systemic lupus erythematosus and antiphospholipid syndrome - I. A. Doroshkevich; S G Radenska-Lopovok; A E Karateev; M Y Krilov; T M Reshetnyk (Научно-практическая ревматология)
Objective. To characterize gastric mucosa (GM) state in systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). Material and methods. Gastroscopy (GS) with GM biopsy and histological examination was performed in 85 pts (65 with SLE and 20 with primary APS). 26 from 65 pts with SLE had secondary APS. 21 SLE pt before inclusion did not receive glucocorticoids (GC). H. pylory and its cytotoxicity gen CagA, HSV-I, CMV were examined in GM samples with PCR. Results. The most frequent GS-feature in pts with SLE and ARS was antral gastritis (82%). In 25% of pts erosions and in 8% - hemorrhages of GM were present. Erosions localized mostly in stomach (25%), in 7% of cases they were present in duodenum. In APS pts epigastric pain and GM erosions were more frequent than in SLE without APS. H.pylory in GM was revealed in 70-81%. In 42% of pts it was present in combination with HSV-1 and/or CMV. In more than half of pts with antral gastritis and GM erosions revealed H. pylory was CagA-positive. GC therapy did not influence frequency of GM erosions and hemorrhages formation. Conclusion. The most frequent GS-features in pts with SLE and ARS were antral gastritis and GM erosions. Epigastric pain and GM erosions were more frequent in pts with APS.